Negative regulation of Gli1 and Gli2 activator function by Suppressor of fused through multiple mechanisms - Barnfield, Paul C.; Zhang, Xiaoyun; Thanabalasingham, Vijitha; Yoshida, Minoru; Hui, Chi-chung (Differentiation (London), 2005)
During animal development, the Hedgehog (Hh) signal transduction pathway plays critical roles in cell fate determination and tissue patterning. In humans, aberrant Hh signaling has been linked to several genetic disorders and cancers. Binding of Hh to its receptor initiates a signaling cascade, which ultimately results in the activation of the Gli/Ci transcription factors. Suppressor of fused (Su(fu)) is a Gli/Ci-interacting protein, which acts as a negative regulator of Hh signaling in Drosophila and vertebrates. Su(fu) is also implicated as a tumor suppressor as its mutations have been found in medulloblastoma and prostate cancer. Su(fu) is thought to act by preventing the nuclear accumulation of Gli/Ci, however, mechanistic insight into its mode of action has remained elusive. We demonstrate here that Su(fu) prevents the nuclear accumulation of Gli1 and Gli2 through multiple mechanisms. While Su(fu) itself is not subject to CRM1-dependent regulation, Su(fu) sequesters Gli1 in the cytoplasm mostly through a mechanism that depends on the activity of the nuclear export protein CRM1. In contrast, CRM1-mediated export is not required for Su(fu) to sequester Gli2. Furthermore, we show that the N-terminus of Su(fu) is sufficient for Gli inactivation in the absence of cytoplasmic sequestration. Together, these observations reveal that Su(fu) regulates the activity of Gli1 and Gli2 through distinct cytoplasmic and nuclear mechanisms.